Uji Kualitatif Boraks Dan Formalin Pada Bakso Yang Dijual Di Kecamatan Limboto Kabupaten Gorontalo - Moh. Yandri Arsyad; Siswatiana R. Taha; Muhammad Sayuti Mas’ud (JURNAL KAJIAN VETERINER, 2019)
The aim of this study is to detect borax and formalin in meatballs that sold in Limboto, Gorontalo district. This is a descriptive qualitative study. Thirty-three samples were taken randomly from pushcart and restaurant meatball in Limboto. It used simple technic where using turmeric to detect borax and potassium permanganate (KMnO4) to detect formalin. The result showed that the samples were free from borax but twenty five samples (75.75%) were positive for formalin. In conclusion, the produsen of meatballs in Limboto was not using borax for making the chewable meatballs but using formalin to preserve the meatballs.